The Use of Folktale Movie in Teaching Speaking of Narrative Text To the Tenth Grade Students of SMAN 1 Gedangan Sidoarjo (RETAIN, 2013)
Abstract Students are believed still have difficulty in speaking activity. So, teacher should be creative in teaching of speaking. Folktale movie is suggested to be used in teaching speaking. The appropriate movie for speaking task is narrative. There are two research questions in this study, first is “How is the implementation of folktale movie in teaching speaking of narrative text to the tenth grade students of SMAN 1 Gedangan Sidoarjo?” and “How is the students’ speaking ability after folktale movie is implemented in teaching speaking?  ” . Dealing with speaking activity, the use of folktale movie may be motivating and interesting. A need to show a sequence of actions and events can be shown clearly in movie. While, the generic structures of narrative are orientation, complication, resolution, and reorientation that is represented in movie. The researcher uses descriptive qualitative design in order to obtain the information. The data of the study for the first research question is the teachers’ activity and the students’ activity that are obtained from observation checklist. Then the data of the study for the second research question is students speaking score that are obtained from students speaking task. The data are obtained through three times observation during three meetings that focus in how the folktale movie implemented in teaching speaking of narrative text and also how the students speaking ability after folktale movie implemented in teaching speaking in the class. The teacher used retelling the story as a technique to help the students to train their speaking skill. Folktale movie is believed as one alternative media which help both of the teacher and the students in teaching and learning speaking of narrative text. It is hoped that further research would be done with different techniques to enrich our understanding of using folktale movie as an alternative media in narrative speaking. Keywords: Speaking, Folktale Movie, and Narrative Text